Family Farming Cooperatives: the Case of the Mixed Cooperative of Family Farmers of the Ipanema Valley - Costa Leite Pereira, Gáudia Maria; Oliveira, João Batista de; Lins Lira, Wagner; Schirmer de Mattos , Jorge Luiz (International Journal of Scientific Research and Management (IJSRM), 2021)
This article addresses cooperativism in the context of family farming, based on the experience of the Cooperativa Mista de Agricultores Familiares do Vale do Ipanema (COOPANEMA) based in the municipality of Águas Belas, Pernambuco, Brazil. This is a reflection on the importance of COOPANEMA for local social and economic development. We used qualitative and descriptive methodology supported by case studies, interviews, and documentary and bibliographic surveys. The cooperative maintains a participative management, with good administrative quality, thanks to its specialized accounting, technical and legal assistance. We conclude that COOPANEMA is a socially consolidated institution, regarded as a reference in cooperative management, acting in the execution of actions and occupying seats in forums, municipal and regional public policy councils, thus contributing to local development.